Eurozone inflation: fresh projections from global factors - Apergis, Nicholas (Economics and Business Letters, 2024)
This study identifies the contributions of global factors in determining eurozone inflation. The analysis makes use of an augmented Phillips curve model of inflation, as well as panel data estimates. The findings document the importance of such factors in forecasting inflation, thus, confirming the substantial role of external factors in eurozone inflation. The findings survived certain model specifications. Therefore, monetary, and fiscal policymakers should explicitly consider both domestic and global conditions to anchor inflation expectations in forming specific strategies for taming inflation expectations.